The Cambridge history of Latin American law in global perspective - Duve, Thomas; Herzog, Tamar (Cambridge University Press, 2024)
Covering the precolonial period to the present, The Cambridge History of Latin American Law in Global Perspective provides a comprehensive overview of Latin American law, revealing the vast commonalities and differences within the continent as well as entanglements with countries around the world. Bringing together experts from across the Americas and Europe, this innovative treatment of Latin American law explains how law operated in different historical settings, introduces a wide variety of sources of legal knowledge, and focuses on law as a social practice. It sheds light on topics such as the history of indigenous peoples' laws, the significance of religion in law, Latin American independences, national constitutions and codifications, human rights, dictatorships, transitional justice and legal pluralism, and a broad panorama of key aspects of the history of statehood and law. This title is also available as Open Access on Cambridge Core.